2009
DOI: 10.1681/asn.2008050492
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TIMP3 Enhances Interstitial Nephritis and Fibrosis

Abstract: The balance of matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMPs) determines the integrity of the extracellular matrix. TIMP3 is the most highly expressed tissue inhibitor of metalloproteinase (TIMP) in the kidney, but its function in renal disease is incompletely understood. In this study, TIMP3 Ϫ/Ϫ mice demonstrated an age-dependent chronic tubulointerstitial fibrosis. After unilateral ureteral obstruction (UUO), young TIMP3 Ϫ/Ϫ mice exhibited increased renal injury (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
130
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 52 publications
10
130
0
1
Order By: Relevance
“…Initial reports indicate ADAM17 and cleavage of its substrates may be involved in kidney disease and can also contribute to the progression of diabetes (1,3,9,10,15,20,21,26,29,33,35,40,42,45,47). We hypothesized that ADAM17 plays a key role in ECM accumulation in DN.…”
Section: Adam17 Expression Is Upregulated In Response To High Glucosementioning
confidence: 98%
See 2 more Smart Citations
“…Initial reports indicate ADAM17 and cleavage of its substrates may be involved in kidney disease and can also contribute to the progression of diabetes (1,3,9,10,15,20,21,26,29,33,35,40,42,45,47). We hypothesized that ADAM17 plays a key role in ECM accumulation in DN.…”
Section: Adam17 Expression Is Upregulated In Response To High Glucosementioning
confidence: 98%
“…ADAM17, a member of this ADAM family of MMPs, was originally described as the sheddase of tumor necrosis factor-␣, referred to as TNF␣-converting enzyme (4, 34). In addition, ADAM17 is also responsible for cleaving membrane-bound growth factors and receptors such as transforming growth factor-␣ (TGF␣), heparin-bound epidermal growth factor (HB-EGF), TNF receptor I and II, adhesion molecules, proinflammatory molecules, amyloid precursor protein, and ErbB4 (4,12,17,28,34,39,41).There is evidence that ADAM17 plays a role in the pathogenesis of DN (1,3,10,11,20,21,26,29,33,35,40,42,47,48). Studies in mesangial cells showed that glucose activates ADAM17 and EGF receptor (EGFR) and regulates profibrotic TGF␤ and the accumulation of matrix proteins (48,(51)(52)(53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some models show that decreased MMP activity, particularly of MMP-2 and MMP-9, ameliorate kidney lesions (107,114,144,150), whereas in other models maintenance of MMPs, namely, MMP-1 and in some cases even MMP-9, is associated with improvement (see Table 2) (4,34). Similarly contradictory, TIMP-3 was elevated in diabetes, but TIMP-3 null mice actually had worsened fibrosis and increased activation of MMP-2 (55,57). Collectively, these data highlight the complexities of MMP pathobiology and the continued need for mechanistic studies.…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…Probably more important in matrix turnover is the role of fibrillar collagen receptors and endocytic receptors, such as discoidin domain receptors (DDRs), leukocyte-associated IG-like receptor 1 (LAIR1), mannose receptor, and Endo180, in phagocytosis of matrix and disposal via the lysosomal pathway in macrophages (see below) and possibly in myofibroblasts (13,22,88). TIMP1 has been shown to be an important cell survival factor in myofibroblasts and this may explain some of the biology associated with its expression, whereas TIMP3 plays inhibitory roles in the activation of myofibroblasts (51,88).…”
mentioning
confidence: 99%